2015
DOI: 10.1021/acs.jced.5b00292
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Silica-Based Materials for the Removal of Hexavalent Chromium: A Review

Abstract: Hexavalent chromium [Cr(VI)], one of the most toxic contaminants, is released in the environment due to various anthropogenic activities. Exposure of Cr(VI) can pose a serious threat to the public health as well as flora and fauna. Effective treatment of Cr(VI) is, therefore, very essential from safety, health, and environment points of view. The present review focuses on the development of silica-based materials for the adsorption of Cr(VI) from wastewater. After discussing toxicity issues and general removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 177 publications
1
81
0
Order By: Relevance
“…Generally speaking, ionosilicas are highly efficient anion exchange materials displaying high adsorption capacity compared to other silica based anion exchange materials (Table ). In their review, Dinker and Kulkarni reported chromate adsorption capacities up to 1.8 mmol g −1 using organically functionalized silica materials . Here, we show that highly performant ionosilica materials displaying chromate exchange capacities up to 2.5 mmol g −1 can easily be obtained, in large scale, via very simple and straightforward synthesis and work‐up procedures.…”
Section: Resultsmentioning
confidence: 57%
“…Generally speaking, ionosilicas are highly efficient anion exchange materials displaying high adsorption capacity compared to other silica based anion exchange materials (Table ). In their review, Dinker and Kulkarni reported chromate adsorption capacities up to 1.8 mmol g −1 using organically functionalized silica materials . Here, we show that highly performant ionosilica materials displaying chromate exchange capacities up to 2.5 mmol g −1 can easily be obtained, in large scale, via very simple and straightforward synthesis and work‐up procedures.…”
Section: Resultsmentioning
confidence: 57%
“…In adsorption process, Chromium (VI) ion from the aqueous solutions moves towards the adsorbent surface due to the electrostatic interaction or a chemical reaction (Dinker & Kulkarni, 2015). Adsorption is an essential and economical process for the removal of Chromium (VI) from the water and industrial wastewater; as for its many advantages: i.e., low energy demand, availability, easy operation, high removal efficiency, less chemical investment, and reusability (Dinker & Kulkarni, 2015). The process of adsorption is continued till the Chromium (VI) which is present in the solution to obtain equilibrium with the adsorbent.…”
Section: Chromium Adsorptionmentioning
confidence: 99%
“…Chromium, on the other hand is present in our surroundings in two forms: trivalent [Cr (III)] and hexavalent [Cr (VI)]. Cr (VI) is about five hundred times more noxious than [Cr (III)] due to its ability to oxidize additional species . Innumerable industries responsible for introduction of excess Cr with wastewater including leather and tanning, pigments synthesis dyeing and textile, paint, metal processing and finishing, pulp, and paper industries, alloys and steel manufacturing and electroplating, etc ,.…”
Section: Introductionmentioning
confidence: 99%
“…Cr (VI) is about five hundred times more noxious than [Cr (III)] due to its ability to oxidize additional species . Innumerable industries responsible for introduction of excess Cr with wastewater including leather and tanning, pigments synthesis dyeing and textile, paint, metal processing and finishing, pulp, and paper industries, alloys and steel manufacturing and electroplating, etc ,. The direct contact with Cr (VI) can cause eyes infection, allergy, asthma, dermatitis and skin irritation including burns .…”
Section: Introductionmentioning
confidence: 99%